CONSTRUCTION PECULIARITIES OF MACHINES OF MULTIPLE TORSION. Part 1 - A. V. Vedeneev (Литьë и металлургия)
The peculiarities of the wires behavior at spin on machines of double torsion are examined. The main characteristics of machines of double torsion are given.